2008
DOI: 10.1016/j.dam.2007.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Non-deterministic ideal operators: An adequate tool for formalization in Data Bases

Abstract: In this paper, we propose the application of formal methods to Software Engineering. The most used data model is the relational model and we present, within the general framework of lattice theory, this analysis of functional dependencies. For this reason, we characterize the concept of f -family by means of a new concept which we call non-deterministic ideal operator (nd.ideal-o). The study of nd.ideal-o.s allows us to obtain results about functional dependencies as trivial particularizations, to clarify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…We denote by N do(L) the set of unary non-deterministic operations in a non-empty set L. The unary case is the trivial one that corresponds with binary relations in L. However, using the idea of ndo and its notation, several concepts and results are not only based on theoretical results, but they also become easier to use. In [4], we showed that this approach allows us to directly prove results about FDs, to clarify the semantics of the FDs and to propose new formal definitions in the lattice framework for normal forms.…”
Section: Definition 22 a Non-empty Subset X ⊆ A Is A Key For A Givenmentioning
confidence: 98%
See 3 more Smart Citations
“…We denote by N do(L) the set of unary non-deterministic operations in a non-empty set L. The unary case is the trivial one that corresponds with binary relations in L. However, using the idea of ndo and its notation, several concepts and results are not only based on theoretical results, but they also become easier to use. In [4], we showed that this approach allows us to directly prove results about FDs, to clarify the semantics of the FDs and to propose new formal definitions in the lattice framework for normal forms.…”
Section: Definition 22 a Non-empty Subset X ⊆ A Is A Key For A Givenmentioning
confidence: 98%
“…In [4] we showed that this concept formalizes the set of dependencies satisfied by a relation. That is, by considering L = 2 A , the set of all FDs that a relation R satisfies is an nd-ideal-o in L, and vice versa, and for all F ∈ N dIo(L) there exists a relation R whose set of satisfied FDs is F .…”
Section: Definition 22 a Non-empty Subset X ⊆ A Is A Key For A Givenmentioning
confidence: 98%
See 2 more Smart Citations
“…(a) Alternative graph-based proof systems [28] as well as automated provers based on simplification equivalences as in [9] are also available. Let us also note that in addition to Theorem 1 which provides a syntactic characterization only for formulas which are semantically entailed to degree 1, the logic of graded attribute implications is also complete in the graded style (Pavelka-style (5) corresponds to the incidence data semantics we have mentioned in the introduction.…”
Section: Preliminariesmentioning
confidence: 99%